2021
DOI: 10.3390/pr9111945
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Views towards Energy Sources with Social Media Data: The Case of Nuclear Energy in the UAE

Abstract: Insights from the analysis of views towards energy sources are of paramount importance for the setting of successful energy policies, especially in instances where the public might be reluctant towards certain projects’ implementations. This work presents an analysis of social media comments data given in response to posts around the connection to the grid of a nuclear plant reactor in the United Arab Emirates (UAE). We assessed comments on Facebook posts of local and international media, as well those written… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
(22 reference statements)
1
1
0
Order By: Relevance
“…Standard deviation values ranged between 0.34% and 0.67%, with the consumer staples (energy) sector ETF returns having the lowest (highest) risk. This is in line with Davide et al ( 2021) Contu, Elshareif & Gurrib (2021) who found positive sentiment from social media on energy sources. All sectors had leptokurtic return distributions with kurtosis ranging from energy sector ETF (70.9) and materials sector ETF (678.1).…”
Section: Descriptive Statisticssupporting
confidence: 91%
“…Standard deviation values ranged between 0.34% and 0.67%, with the consumer staples (energy) sector ETF returns having the lowest (highest) risk. This is in line with Davide et al ( 2021) Contu, Elshareif & Gurrib (2021) who found positive sentiment from social media on energy sources. All sectors had leptokurtic return distributions with kurtosis ranging from energy sector ETF (70.9) and materials sector ETF (678.1).…”
Section: Descriptive Statisticssupporting
confidence: 91%
“…Contu et al [4] analysed the impact of the announcement of the connection to the grid of a nuclear plant reactor in the United Arab Emirates using social media data. In particular, the authors analysed the comments on Facebook posts from local and international media, as well as those written in response to a post from a social media influencer.…”
mentioning
confidence: 99%